Outcomes and complications associated with malar onlays: literature review and case series of 119 implants. Issue 9 (November 2020) - French, K.E.M.; Gormley, M.; Kana, A.; Deacon, S.; Revington, P.J.
Abstract: Alloplastic malar onlays have been used by surgeons to correct or enhance the midfacial skeleton for over 40 years. Case series have shown respectable results using different alloplastic materials in various maxillofacial subsites. However, these articles include small numbers of patients with limited follow up. We present a literature review specifically concentrating on porous polyethylene (Medpor, Stryker) and polyethyl ether ketone (PEEK) malar onlays. We illustrate the technique used by a single oral and maxillofacial surgeon for placement of 119 implants in 61 patients over a 14-year period, and show the results of this work with long-term follow up. A complication rate of 2.5% in this cohort was reported, with follow up of three years, demonstrating that this technique for midfacial correction is successful in both the short and the long term.